Gender comparisons of pupils' self-confidence in mathematics learning - Hannula, Markku S.; Maijala, Hanna; Pehkonen, Erkki; Nurmi, Anu (NOMAD Nordic Studies in Mathematics Education, 2005)
The paper analyzes pupils' self-confidence in mathematics, which involves pupils' mathematical beliefs about themselves, and beliefs about achievement in mathematics, in Finnish elementary school. The research described consists of a survey on mathematical beliefs of about 3000 fifth-graders and seventh-graders. Results showed that mathematical beliefs about oneself could be divided, based on the indicator used, into three factors: self-confidence, success orientation, and defense orientation. The fifth-graders had higher self-confidence than the seventh-graders. Additionally, boys in both grades had remarkably higher self-confidence in mathematics than girls.